Comparative pedagogy and educational systems through an optimal dioptry - Bazić, Jovan R (Sociološki pregled, 2023)
This book has been reviewed by applying the sociological theoretical-methodological approach in order to: a) point to the socio-historical conditionality and the scientific reasons of the constitution and development of comparative pedagogy as a separate scientific discipline; and b) to emphasize the mutual effect of educational systems and social processes in specific socio-historical, cultural, economic and political conditions.